2021
DOI: 10.1002/jmv.26895
|View full text |Cite
|
Sign up to set email alerts
|

A pilot double‐blind safety and feasibility randomized controlled trial of high‐dose intravenous zinc in hospitalized COVID‐19 patients

Abstract: Zinc inhibits replication of the SARS-CoV virus. We aimed to evaluate the safety, feasibility, and biological effect of administering high-dose intravenous zinc (HDIVZn) to patients with COVID-19. We performed a Phase IIa doubleblind, randomized controlled trial to compare HDIVZn to placebo in hospitalized patients with COVID-19. We administered trial treatment per day for a maximum of 7 days until either death or hospital discharge. We measured zinc concentration at baseline and during treatment and observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 31 publications
0
52
0
1
Order By: Relevance
“…Predicted drugs in Cluster 3 that are not used for cancer therapy and are not in clinical trials were then assessed for their association with viral replication through literature searches. We found literature documenting that Zinc deficiency has been confirmed in COVID-19 patients, and SARS-CoV-2 replication was reduced when zinc was administered [39] . Ademetionine has also been identified as a repurposing candidate in several studies [7] , [40] .…”
Section: Resultsmentioning
confidence: 93%
“…Predicted drugs in Cluster 3 that are not used for cancer therapy and are not in clinical trials were then assessed for their association with viral replication through literature searches. We found literature documenting that Zinc deficiency has been confirmed in COVID-19 patients, and SARS-CoV-2 replication was reduced when zinc was administered [39] . Ademetionine has also been identified as a repurposing candidate in several studies [7] , [40] .…”
Section: Resultsmentioning
confidence: 93%
“…Studies show that treatment with zinc as adjuvant therapy was appeared to be feasible and safe for the management of COVID-19. However, the infusion of zinc causes limited infusion site irritation on the periphery [87]. Zinc supplement was found to be efficiently clear the SARS-CoV-2 from the nasopharynx in a lesser time than other symptomatic therapy [88].…”
Section: Nutritional Supplementsmentioning
confidence: 95%
“…They observed that none of the interventions significantly decreased the duration of symptoms compared with standard care. In a pilot randomized controlled trial with hospitalized COVID-19 patients, Patel et al (2021) [132] detected low serum zinc levels in both experimental and placebo groups (6.9 ± 1.1 and 7.7 ± 1.6 mmol/L, respectively). They also observed that a high dose of venous zinc administration (0.24 mg/kg/day of elemental zinc for a maximum of 7 days) was safe and able to increase serum zinc levels above the zinc deficiency cutoff adopted (10.7 mmol/L).…”
Section: Randomized Controlled Trials Of Zinc Supplementation In Covid-19mentioning
confidence: 97%
“…According to our search, 3 randomized clinical trial studies aimed to investigate the effect of zinc supplementation in patients with COVID-19 [37,131,132]. Abd-Elsalam et al ( 2020) [131] aimed to evaluate the effect of combining chloroquine/hydroxychloroquine and zinc in the treatment of COVID-19 patients.…”
Section: Randomized Controlled Trials Of Zinc Supplementation In Covid-19mentioning
confidence: 99%